Propose a MPPT Algorithm Based on Thevenin Equivalent Circuit for Improving Photovoltaic System Operation - Nguyen, Binh Nam; Nguyen, Van Tan; Duong, Minh Quan; Le, Kim Hung; Nguyen, Huu Hieu; Doan, Anh Tuan (Frontiers in Energy Research, 2020)
Smart grids are considered as key solutions to solve current power security issues. Among these suggestions, microgrid is proposed to integrate distributed generations (DGs) such as photovoltaic (PV) system into the network and the control of DGs output power is getting more attention. The output power of PV arrays with nonlinear characteristics is affected by temperature, solar irradiation and load. Various maximum power point tracking (MPPT) methods for photovoltaic (PV) power systems have been considered and developed to maximize the delivered possible power. In this paper, a modelized photovoltaic source is introduced, based on the Thevenin equivalent circuit. An ordinarily employed solar system model is linearized into simple Thevenin source-resistance representation. Next, a control algorithm associated with the relationship between controller's PWM duty cycle of the MPPT boost converter and solar array output power, namely proposed MPPT algorithm, is introduced. This proposed method is compared with an existing popular MPPT algorithm to confirm its superior performance by using the MATLAB/SIMULINK® simulation. The results show an improvement in the power generation from a PV array in any weather condition, and also help to reduce the impact of rapid change of solar irradiation on the output power variation within the time duration of change. Therefore, the proposed algorithm reduces the effect on grid frequency and motivate the PV generation penetration into the microgrids. Finally, a 50W DC-DC boost converter prototype is implemented and tested to verify the feasibility of the proposed control scheme.